Performance of the CMS muon trigger system in proton-proton collisions at âˆš(s) = 13. (2nd July 2021) - Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; EscalanteÂ DelÂ Valle, A.; FrÃ¼hwirth, R.; Jeitler, M.; Krammer, N.; Lechner, L.; Liko, D.; Mikulec, I.; et al.
Abstract: The muon trigger system of the CMS experiment uses a combination of hardware and software to identify events containing a muon. During RunÂ 2 (covering 2015â€"2018) the LHC achieved instantaneous luminosities as high as 2Â Ã—Â 10 34 while delivering proton-proton collisions at âˆš(s) = 13. The challenge for the trigger system of the CMS experiment is to reduce the registered event rate from about 40MHz to about 1kHz. Significant improvements important for the success of the CMS physics program have been made to the muon trigger system via improved muon reconstruction and identification algorithms since the end of RunÂ 1 and throughout the RunÂ 2 data-taking period. The new algorithms maintain the acceptance of the muon triggers at the same or even lower rate throughout the data-taking period despite the increasing number of additional proton-proton interactions in each LHC bunch crossing. In this paper, the algorithms used in 2015 and 2016 and their improvements throughout 2017 and 2018 are described. Measurements of the CMS muon trigger performance for this data-taking period are presented, including efficiencies, transverse momentum resolution, trigger rates, and the purity of the selected muon sample. This paper focuses on the single- and double-muon triggers with the lowest sustainable transverse momentum thresholds used by CMS. The efficiency is measured in a transverse momentum range from 8 to several hundred.